Novel perceptions and insights into the rare hematologic malignancy of acute megakaryocytic leukemia: a multicenter clinical retrospective study - Yuan Liu; Yanquan Liu; Xiaojun Chen; Yue Yin; Zhenyuan Xu; Jiachen Xie; Jianzhen Shen; He Huang; Huidong Guo (Frontiers in Medicine)
ObjectiveAcute megakaryocytic leukemia (AMKL) constitutes a rare subtype of acute myeloid leukemia in clinical practice and exhibits a high degree of heterogeneity. This study endeavors to explore the clinical manifestations, diagnosis, treatment, and prognosis of AMKL, offering novel perspectives for both basic and clinical investigations of rare myeloid tumors in the fields of oncology and hematology.MethodsThe clinical data of 23 patients with AMKL admitted to the Fujian Medical University Union Hospital, the Affiliated Hospital of Putian University, and the First Affiliated Hospital of Gannan Medical University from January 2014 to July 2024 were retrospectively analyzed. The clinical characteristics, diagnosis and differential diagnosis, treatment, and prognosis of AMKL patients were examined. Additionally, the latest literature in the PubMed database was retrieved for review and discussion regarding the research advancements of AMKL and its diagnosis and treatment.ResultsA total of 23 patients with AMKL were encompassed in this study, the clinical manifestations of all patients were predominantly hematological non-specific symptoms, such as anemia, bleeding, infection, and invasive swelling or occupation of tissues and organs. All patients underwent bone marrow puncture biopsy, cytochemical staining of bone marrow cells of AMKL patients demonstrated that the staining of POX, NAS-DCE, and hot brine test were negative, however, the PAS staining, α-NAE staining and NaF inhibition test were positive. Except for 2 patients who were not detected by flow immunotyping, cytogenetics and molecular biology, the remaining 21 patients were detected accordingly, and megakaryocyte antigens (CD41, CD42, CD61) were expressed in these 21 patients with AMKL, accompanied by certain cytogenetic or molecular biological abnormalities. There were two patients forsook treatment in our study, and remaining 21 patients who underwent clinical treatment measures, 1 patient (4.76%) died after 1 course of chemotherapy, 3 patients (14.29%) succumbed to severe infection occasioned by bone marrow suppression after 2 courses of chemotherapy, and 7 patients (33.33%) achieved CR after 1 course of chemotherapy, 4 patients (19.05%) attained CR after 2 courses of chemotherapy, and 6 patients (28.57%) failed to achieve remission (NR) after 2 courses of induction chemotherapy. Correspondingly, a total of 6 patients received allogeneic hematopoietic stem cell transplantation (HSCT) in this study, among which 3 patients received HSCT after CR in the first induction chemotherapy, 1 patient received HSCT after CR in the second round of induction chemotherapy, and 2 patients with NR after induction chemotherapy underwent HSCT. We conducted follow-up until July 31, 2024 and discovered that among the 17 patients who received complete and standardized treatment and survived, 3 (17.65%) patients were lost to follow-up and 8 (47.06%) patients perished within 2 years due to treatment failure attributed to disease progression, recurrence, and uncontrollable disease. The remaining 6 patients (35.29%) are still alive at present and have not experienced disease progression or recurrence. The median follow-up period was 33.5 months (ranging from 4.5 to 76 months) as of July 31, 2024, the results of survival analysis indicate: the OS and EFS of AMKL patients treated with chemotherapy alone were inferior to those treated with chemotherapy combined with HSCT (all p < 0.05). Additionally, AMKL patients with severely abnormal cytogenetic test results had poorer OS and EFS (all p < 0.05). Concurrently, the OS and EFS of AMKL patients who achieved CR after 2 courses of induction chemotherapy were significantly superior to those of AMKL patients who did not achieve CR (all p < 0.05).ConclusionAMKL is infrequent in clinical practice, features a poor prognosis, lacks specificity in clinical manifestations, and is prone to misdiagnosis or omission. Clinical trials of new drugs should be prioritized, while close monitoring of measurable residual disease (MRD) should be implemented. Patients with AMKL might benefit from induced remission chemotherapy combined with novel targeted therapy. Hematopoietic stem cell transplantation should be carried out as soon as possible after the first CR induced by standard chemotherapy to optimize the prognosis.